Reimaging Cairo's garbage collectors: The role of design thinking and story mapping in developing social learning to identify community assets and challenges. (4th May 2023) - Mohamed, Abdelbaseer A.; Kronenberg, Jakub
ABSTRACT: Mapping the challenges and assets of a community for driving development strategies applies to many methods, yet it can be difficult to reflect residents' collective concerns and interests. This paper reports and critically reflects on an educational exercise of design thinking and story mapping in Cairo's Zabbaleen community, a hard-to-reach disadvantaged group comprised of exclusively low-income Christian garbage collectors. The article investigates the potentials and challenges of the tools employed to better facilitate the social learning process that is centered on understanding the underlying challenges and assets in disadvantaged communities. It concludes that designers and educators learned that they need to better incorporate community development principles of local self-determination, self-help and community participation into the design process. Students learned that community members cannot be passive recipients of academic concepts. The study demonstrates a need for an integration of professional or technical knowledge with indigenous knowledge and perspectives.